Cinema and the cultural Cold War: US diplomacy and the origins of the Asian cinema network - Lee, Sangjoon, (The United States in the world, 2020)
The Asia Foundation's Motion Picture Project -- The FPA, US Propaganda, and Postwar Japanese Cinema -- It's "Oscar" Time in Asia! -- Constructing the Anti-Communist Producers' Alliance -- Projecting Asian Cinema to the World -- The Rise and Demise of a Developmental State Studio -- Hong Kong, Hollywood, and The End of the Network -- Epilogue : From Asia to Asia-Pacific.
https://katalog.adlr.link/Record/155-1725808226